2016
DOI: 10.1038/srep18815
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box 1-induced epithelial mesenchymal transition in human airway epithelial cells

Abstract: Epithelial–mesenchymal transition (EMT) is implicated in bronchial remodeling and loss of lung function in chronic inflammatory airway diseases. Previous studies showed the involvement of the high mobility group box 1 (HMGB1) protein in the pathology of chronic pulmonary inflammatory diseases. However, the role of HMGB1 in EMT of human airway epithelial cells is still unclear. In this study, we used RNA sequencing to show that HMGB1 treatment regulated EMT-related gene expression in human primary-airway epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 59 publications
3
46
1
1
Order By: Relevance
“…Although previous studies have shown that e-cig-induced proinflammatory cytokine production, the role of HMGB1 in such exposures is not known (34,78). Our findings of increased HMGB1 release along with a decrease in E-cadherin suggest potential increase in inflammation and epithelial cell permeability, similar to situations with other injuries (17,48). Thus nicotine aerosol exposure via release of HMGB1 likely contributes toward increased epithelial and vascular permeability leading to pulmonary edema.…”
Section: Discussionsupporting
confidence: 53%
“…Although previous studies have shown that e-cig-induced proinflammatory cytokine production, the role of HMGB1 in such exposures is not known (34,78). Our findings of increased HMGB1 release along with a decrease in E-cadherin suggest potential increase in inflammation and epithelial cell permeability, similar to situations with other injuries (17,48). Thus nicotine aerosol exposure via release of HMGB1 likely contributes toward increased epithelial and vascular permeability leading to pulmonary edema.…”
Section: Discussionsupporting
confidence: 53%
“…HMGB1 also functions as an inducer of EMT in human cancer cells (27)(28)(29)(30)(31). HMGB1 expression was much higher in bladder cancer cells than normal urethra epithelial cells and was associated with cell invasion (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study demonstrated increased expression of the SPARC family member, follistatin‐like protein 1 (FSTL1) in lung macrophages of patients with severe asthma, and further demonstrated that FSTL1 induces airway remodelling in mouse models of asthma (Miller et al, ). Moreover, it has recently been shown that the enigmatic protein high mobility group box 1 (HMGB1) induces SPARC expression in airway epithelial cells (Chen et al, ). This is of relevance, because HMGB1 is implicated in asthma and COPD (Sukkar et al, ) and has also been identified as a mediator of EMT and ECM synthesis in airway epithelial cells, thus suggesting a potential link between HMGB1 and SPARC signalling in chronic airways disease (Ojo et al, ; Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has recently been shown that the enigmatic protein high mobility group box 1 (HMGB1) induces SPARC expression in airway epithelial cells (Chen et al, ). This is of relevance, because HMGB1 is implicated in asthma and COPD (Sukkar et al, ) and has also been identified as a mediator of EMT and ECM synthesis in airway epithelial cells, thus suggesting a potential link between HMGB1 and SPARC signalling in chronic airways disease (Ojo et al, ; Chen et al, ). Together with our discussion above, these studies provide further impetus for investigation of SPARC in asthma and COPD.…”
Section: Discussionmentioning
confidence: 99%